PENINGKATAN KESAADARAN MAHASISWA MELALUI PENDAYAGUNAAN POSTER ANTI KEKERASAN SEKSUAL DAN PERUNDUNGAN DI LINGKUNGAN PRODI PENDIDIKAN GURU PAUD UNIVERSITAS NEGERI JAKARTA - Endah Windiastuti (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
The rampant cases of sexual violence and bullying have raised concerns in the community. Sexual violence and bullying can happen to anyone, anywhere, and anytime. This article contains the socialization process related to the phenomenon of sexual violence and bullying in the department of Early Childhood Education environment at Jakarta State University. The target of this socialization is 32 of 1st semester students. The purpose of this socialization is to increase student awareness of the phenomenon of sexual violence and bullying. This socialization began with the presentation of material, including cases of sexual violence and bullying in Indonesia that were published in online news. Furthermore, students were invited to discuss the two phenomena from their perspectives. Students seemed enthusiastic and agreed that sexual violence and bullying must be considered carefully so that they do not become victims or perpetrators. In addition to the presentation of material in a classical manner, socialization was also carried out by installing posters in the department of Early Childhood Education environment at Jakarta State University.